Isolation and Characterization of Pediocin AcH Chimeric Protein Mutants with Altered Bactericidal Activity - Miller, Kurt W. (American Society for Microbiology, 1998)
A collection of pediocin AcH amino acid substitution mutants was generated by PCR random mutagenesis of DNA encoding the bacteriocin. Mutants were isolated by cloning mutagenized DNA into an Escherichia coli malE plasmid that directs the secretion of maltose binding protein-pediocin AcH chimeric proteins and by screening transformant colonies for bactericidal activity against Lactobacillus plantarum NCDO955 (K. W. Miller, R. Schamber, Y. Chen, and B. Ray, 1998. Appl. Environ. Microbiol. 64:14–20, 1998). In all, 17 substitution mutants were isolated at 14 of the 44 amino acids of pediocin AcH. Seven mutants (N5K, C9R, C14S, C14Y, G37E, G37R, and C44W) were completely inactive against the pediocin AcH-sensitive strains L. plantarum NCDO955, Listeria innocua Lin11, Enterococcus faecalis M1, Pediococcus acidilactici LB42, and Leuconostoc mesenteroides Ly. A C24S substitution mutant constructed by other means also was inactive against these bacteria. Nine other mutants (K1N, W18R, I26T, M31T, A34D, N41K, H42L, K43N, and K43E) retained from <1% to ∼60% of wild-type activity when assayed against L. innocua Lin11. One mutant, K11E, displayed ∼2.8-fold-higher activity against this indicator. About one half of the mutations mapped to amino acids that are conserved in the pediocin-like family of bacteriocins. All four cysteines were found to be required for activity, although only C9 and C14 are conserved among pediocin-like bacteriocins. Several basic amino acids as well as nonpolar amino acids located within the hydrophobic C-terminal region also were found to be important. The mutations are discussed in the context of structural models that have been proposed for the bacteriocin.